2022
DOI: 10.3390/diagnostics12020463
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable Clinical Decision Support System for Audiology Based on Predicted Common Audiological Functional Parameters (CAFPAs)

Abstract: Common Audiological Functional Parameters (CAFPAs) were previously introduced as abstract, measurement-independent representation of audiological knowledge, and expert-estimated CAFPAs were shown to be applicable as an interpretable intermediate layer in a clinical decision support system (CDSS). Prediction models for CAFPAs were built based on expert knowledge and one audiological database to allow for data-driven estimation of CAFPAs for new, individual patients for whom no expert-estimated CAFPAs are availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The present study clearly demonstrated the importance of combining expert knowledge and statistical learning in the design of a CDSS for audiology. The expert validation and corresponding statistical analyses to investigate agreement between model-predicted and expert-derived CAFPAs provided important insights into the current properties and the necessary future improvement of the CDSS proposed by Buhl ( 22 ) and the prediction models of CAFPAs ( 23 ). Furthermore, the collected qualitative data on the experts' decision-making process are highly valuable to complement statistical conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study clearly demonstrated the importance of combining expert knowledge and statistical learning in the design of a CDSS for audiology. The expert validation and corresponding statistical analyses to investigate agreement between model-predicted and expert-derived CAFPAs provided important insights into the current properties and the necessary future improvement of the CDSS proposed by Buhl ( 22 ) and the prediction models of CAFPAs ( 23 ). Furthermore, the collected qualitative data on the experts' decision-making process are highly valuable to complement statistical conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to further ameliorate clinical applicability, Buhl et al ( 19 22 ) and Saak et al ( 23 ) rendered a series of development steps toward a CDSS for audiology, which strongly relies on expert knowledge and is targeted toward future interpretability and integration across different data sources. The CDSS should operate on diverse clinical databases, and it aims at covering the complete audiological decision-making process, including the classification of audiological findings for given patients, as well as suggesting appropriate treatment recommendations (summarized as diagnostic cases).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations